The association of healthy eating index with periodontitis in NHANES 2013–2014 - Li, Xin-yu; Wen, Ming-zhe; Xu, Yu-hua; Shen, Yu-chen; Yang, Xi-tao (Frontiers in Nutrition, 2022)
Abstract: Background: The prevalence and spread of periodontal diseases are among the leading causes of tooth morbidity and mortality worldwide. Periodontal disease is characterized by chronic inflammation that can destroy adjacent alveolar bone and lead to a loss of periodontal ligaments. Although previous studies have found that a diet low in carbohydrates, rich in Omega-3 fatty acids, rich in vitamins C and D, and rich in fiber can significantly reduce periodontal disease. Periodontal disease may present as gingivitis or periodontitis. However, studies on the role of healthy eating index in periodontitis are lacking. The purpose of this study was to assess the association between healthy eating index and periodontitis. Methods: We analyzed data collected from participants in the National Health and Nutrition Examination Survey (NHANES), a nationally representative survey conducted in two-year cycles from 2013 to 2014. As part of our analysis, we developed multivariate logistic regression models to examine the independent association between the healthy eating index and periodontitis and report the extent of the association in terms of odds ratios (OR) with 95% confidence intervals (CI). Results: Individuals with a lower total healthy eating index had a higher prevalence of periodontitis. Adjusted multivariate regression models showed that a higher healthy diet index was associated with a lower prevalence of periodontitis (OR= 0.8, 95% CI: 0.68~0.94, P= 0.006). Conclusion: The results of the study showed that dietary structure was associated with the prevalence of periodontitis. Patients with a higher healthy eating index had a lower prevalence of periodontitis. These findings will need to be confirmed by longitudinal, prospective studies in the future.